A GREAT WRITER IN THE BACKGROUND OF AN EPOCH - PORUBIN, Lilia; JECHIU, Ala (Journal of Social Sciences)
The aspect that mainly characterizes the literary process from the 90s of the last century is the intensification of the process of capitalization on the interwar literary heritage. Many writers are re-included in the circuit of our spiritual values. The publication of their works is followed by monographic investigations. Studies, portraits and essays are written in anthologies and literary histories. Leon Donici is one of the most original and innovative prose writers. Outlined as an artistic personality in the Russian cultural environment, Leon Donici brought in Romanian literature an ostentatious nostalgic spirit: romantic, but also realistic; clear, but also deeply tragic. A well-defined personality, Leon Donici was overwhelmed by contradictory impulses and deserved, on account of this, an unequal acceptance that was dominated by numerous stereotypes.